Friction influence on the AA6060 aluminium alloy formability - Costanzo Bellini; Gillo Giuliano; Luca Sorrentino (Fracture and Structural Integrity)
Using a finite element calculation code, this work analyses the influence of friction during a stamping test conducted on the AA6060 aluminium-based alloy. The study focuses on phenomena happening when the sheet necking appears. This condition, based on the Hill’s localized necking theory and the Swift’s diffuse necking theory, is dependent on the material hardening index. This work shows that the punch stroke at the necking condition point is maximum when the main strain measured on the sheet surface are unbalanced and close to a balanced biaxial tension condition.